The Influence of an Exercise Focusing on 5 Fingers towards Anxiety Level in Pulisen Boyolali Village - Norman Wijaya Gati; Ika Silvitasari (Jurnal Kesehatan, 2022)
Anxiety is a natural response when something happens and threatens the integrity of every individual. Anxiety is a mental health problem that is often overlooked. Anxiety will become a serious mental problem when not taken the right action. There are some ways to reduce the level of axienty, one of them is  focusing on 5 fingers excercise. The aimsof this study was to find out the effect of the 5-finger focus exercise towards anxiety level. The approach of this research was a quasi-experimental with pre and post tests without control groups. There were 30 respondent participated in this study. The results shows that most of these respondents were women. The level of anxiety in this study before the intervention was carried out as many as 20 people (66.7%) were in severe anxiety while after the intervention as many as 20 people (66.7%) the patient's anxiety decreased to not being anxious. Bivariate analysis using the Wilcoxon test showed p-value of 0.000 (<0.05), which means that there is a relationship between exercise focusing on 5 fingers and the level of anxiety. There was an effect of focusing on 5 fingers toward level of anxiety.